BUILDING THE IMAGE OF A QUALITY ISLAMIC BOARDING SCHOOL: INNOVATIVE MARKETING STRATEGIES THAT CHANGE PUBLIC PERCEPTION - Nurul Fadilah; Al Kahfi; Siti Trizuwani; Dinda Luthfiaturrahmah Alhaqa (J-MD Jurnal Manajemen Dakwah, 2024)
This research investigates the marketing management practices at Abu Hurairah Islamic Boarding School, which is accredited by the Islamic University of Madinah, Saudi Arabia, and has seen a growing number of applicants each year. With its adequate facilities and numerous advantages, the researcher aims to explore how the institution manages its enrollment process and marketing strategies. This qualitative study employs observation, interviews, and documentation for data collection, with analysis based on Glaser and Strauss' constant comparative method. The study focuses on two main aspects: (1) new student enrollment management and (2) marketing strategies for student recruitment. The findings reveal that the enrollment management process includes planning (setting quotas for alumni and non-alumni), organizing (committee division by class), implementing (a 2-3 month admission process), and supervising (performance evaluation during activities). The marketing strategies align with the marketing mix theory, covering Product (boarding and full-day classes), Price (tuition fees and other costs), Place (a strategic city-center location), Promotion (word of mouth), People (qualified staff from the Middle East), Process (seven stages of admission), and Physical Evidence (facilities, uniforms, and staff). The originality of this research lies in its detailed analysis of how Islamic boarding schools like Abu Hurairah implement modern marketing management to enhance student enrollment.